2021
DOI: 10.3390/ani11051340
|View full text |Cite
|
Sign up to set email alerts
|

Selection Response Due to Different Combination of Antagonistic Milk, Beef, and Morphological Traits in the Alpine Grey Cattle Breed

Abstract: Selection in local dual-purpose breeds requires great carefulness because of the need to preserve peculiar traits and also guarantee the positive genetic progress for milk and beef production to maintain economic competitiveness. A specific breeding plan accounting for milk, beef, and functional traits is required by breeders of the Alpine Grey cattle (AG), a local dual-purpose breed of the Italian Alps. Hereditability and genetic correlations among all traits have been analyzed for this purpose. After that, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 42 publications
(76 reference statements)
5
15
0
Order By: Relevance
“…As for body weight, ADG presents lower h 2 in first stages of the performance test, and h 2 values agree with what has been found in the literature (Yin and König, 2018). The highest heritabilities were found for the traits related to the carcass conformation, with a value of 0.45 and 0.47 respectively for CF and DP, close to what was observed in other local dual-purpose or beef cattle (Albera et al, 2001;Sbarra et al, 2013;Mancin et al, 2021c). These traits also appeared highly genetic correlated.…”
Section: Heritability and Genetic Correlationssupporting
confidence: 88%
“…As for body weight, ADG presents lower h 2 in first stages of the performance test, and h 2 values agree with what has been found in the literature (Yin and König, 2018). The highest heritabilities were found for the traits related to the carcass conformation, with a value of 0.45 and 0.47 respectively for CF and DP, close to what was observed in other local dual-purpose or beef cattle (Albera et al, 2001;Sbarra et al, 2013;Mancin et al, 2021c). These traits also appeared highly genetic correlated.…”
Section: Heritability and Genetic Correlationssupporting
confidence: 88%
“…In our study, all descriptive statistics of traits match the ones reported for Rendena in previous literature [ 30 , 58 ] and were similar to other local dual-purpose breeds such as the Alpine Grey cattle [ 69 ]. The heritability of traits was also found to be close to that reported in previous studies.…”
Section: Discussionsupporting
confidence: 85%
“…We recorded little difference from the study of [ 4 ], even if our dataset was greater by an amount of about 40%. The heritabilities of these traits were similar to the ones observed in other dual-purpose (i.e., Alpine Grey; [ 36 ] or beef specialized breeds [ 37 , 38 , 39 ]). All traits appeared highly genetically correlated, especially EUROP and DP, as expected and widely reported in the literature [ 38 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 76%